EXPLORATION OF EUDAIMONIC WELL-BEING AMONG SENIOR CITIZENS: A QUALITATIVE STUDY - Zartashia Kynat Javaid; Ayesha Shahid; Sania Ashfaq; Eman Nisar; Noor Fatima (International Journal of Contemporary Issues in Social Sciences, 2024)
Eudaimonic well-being is the existence of positive psychological functioning and a sense of thriving, which includes positive connections, personal progress, purpose in life, and self-acceptance (Keyes, 2002). Any country's quality of life may be inferred from the eudaimonic well-being of its older population. Investigating the eudaimonic well-being of aging people is crucial to addressing the deficiencies in any nation's citizenry's quality of life. The current study investigates Pakistani older adults' eudaimonic well-being. This is a qualitative study, and the technique used for data collection is semi-structured interviews. Data of 12 interviews was analyzed using thematic analysis. Assessment of eudaimonic well-being, the role of gender, other influencing factors, and suggestions for its improvement are discussed. The results showed that the general level of eudaimonic well-being of the senior citizens of Pakistan is low. Although women faced discrimination due to their gender, they scored higher on eudaimonia compared to men. It is concluded that implementing certain strategies can improve the eudaimonic well-being of senior citizens and the overall population.